Correlation Between Gastroesophageal Reflux Disease Questionnaire and Erosive Esophagitis in School-aged Children Receiving Endoscopy - Jhen-Yan Chiu; Jia-Feng Wu; Yen-Hsuan Ni (Pediatrics and Neonatology)
The gastroesophageal reflux disease (GERD) questionnaire (GerdQ) is a validated questionnaire that was developed recently to help identify GERD patients. The sensitivity and specificity of GerdQ for the diagnosis of GERD in adult patients were 65% and 71%, respectively. Because the application of GerdQ in pediatric population is largely unknown, the aim of this study is to establish the endoscopic correlation between Chinese GerdQ and grades of erosive esophagitis (EE) in Taiwanese children. Methods: Seventy-four children (aged 9–18 years) were evaluated by our version of the Chinese GerdQ prior to receiving esophagogastroduodenoscopy for warning upper gastrointestinal symptoms. Grades of EE were assessed blindly, according to the Los Angeles classification. The sensitivity and specificity of GerdQ for detecting endoscopic EE were analyzed. Results: In 74 patients, the male to female ratio was 1:1.1 and the mean age was 14.2 ± 2.3 years (age range: 9.2–17.9 years). Thirty-nine percent of the enrolled patients had EE. The sensitivity and specificity of GerdQ (with a cutoff score of ≥7) to identify EE patients were 65.5% and 80%, respectively. The odds ratio of GerdQ for a cutoff score of 7 to identify EE was 7.6 (95% confidence interval = 2.6–21.9, p < 0.001). Conclusion: For the identification of EE in children, the Chinese GerdQ had similar sensitivity and specificity to that used for adults. This questionnaire may be applied as a noninvasive screening tool.